Perioperative Treatment Strategies for Lung Cancer in 2025: A Paradigm Shift (Canadian Oncology Today, 2025)
Perioperative management of resectable non-small cell lung cancer (NSCLC) has evolved significantly with the integration of immune checkpoint inhibitors and targeted therapies. This review synthesizes current evidence from key clinical trials, highlighting the improved survival outcomes achieved with neoadjuvant and perioperative chemoimmunotherapy in oncogene-wildtype NSCLC, as well as adjuvant tyrosine kinase inhibitors (TKIs) in epidermal growth factor receptor (EGFR)‑ and anaplastic lymphoma kinase (ALK)-altered tumours. While neoadjuvant immunotherapy has demonstrated high pathological response rates and long-term survival benefits, perioperative strategies may offer added value in selected subgroups. The ADAURA and ALINA trials have established adjuvant osimertinib and alectinib as new standards of care in oncogene-driven disease. Unresolved questions remain regarding optimal treatment sequencing, duration, and patient selection. Emerging tools such as circulating tumour DNA and artificial intelligence hold promise for refining risk stratification and guiding individualized treatment approaches.